Development And Isolation Of Dna Microsatellite Markers For The Characterisation And Identification Of Mystus Nemurus (C & V) - Chan, Soon Choy (2003)
Mystus nemurus or better known as 'ikan Baung' is an indigenous species In Malaysia. The popularity of this freshwater fish among the locals had made it an economically important aquaculture candidate. Of the so many DNA marker systems available, microsatellites are particularly useful for population studies and have been proven to be the most efficient due to their codominant modes of inheritance. Two methods were used to isolate microsatellites in M. nemurus, namely Random Amplified Hybridisation Microsatellites (RAHMs) and Random Amplified Microsatellites (RAMs). A total of 88 micro satellite sequences and 18 cryptic simple regions were produced. The majority (90%) of these microsatellites were detected by the RAMs method while the RAHMs method required further optimisation and modification. The isolation of microsatellites resulted in 33 primer pairs being designed.